Role of Computed Tomography in Evaluating Postoperative Complications After Thoracic Surgery (Medical Forum Monthly, 2023)
Objective: The main objective of the study is to find the role of CT in evaluating postoperative complications after thoracic surgery.Study Design: A retrospective observational studyPlace and Duration of Study: This study was conducted at the Thoracic Surgery Department and Radiology Department of the Medical Teaching Institution, Lady Reading Hospital (MTI-LRH) in Peshawar, KPK, Pakistan from January 2022 to January 2023.Materials and Methods: A total of 135 patients who had CT scan after thoracic surgery for post-operative complications were included in the study. Data regarding postoperative complications and relevant clinical information were collected for each participant. Postoperative complications of interest included atelectasis, pneumothorax, pleural effusions, bronchopleural fistulas, surgical site infections, and vascular complications.Results: Data were collected from 135 patients of both genders. There were 85 males and 50 females. Mean age of the patients was 55.0±12.35. Out of the 135 patients, 35 (25.9%) developed postoperative complications. The most common complication was atelectasis, occurring in 18 patients (12.5%). Pneumothorax was observed in 8 patients (5.9%), while 5 patients (3.7%) developed pleural effusions. Bronchopleural fistulas were identified in 3 patients (2.2%), and 4 patients (2.9%) experienced surgical site infections. Vascular complications, including pseudoaneurysms and arteriovenous fistulas, were observed in 3 patients (2.2%).Conclusion: It is concluded that early detection through CT scans facilitated timely interventions, improved patient outcomes, and minimized the need for invasive procedures. The utilization of CT imaging as a standard practice in postoperative evaluations has the potential to enhance patient safety and optimize healthcare resources